Relationship Patterns between Leader-Subordinate Similarity and Subordinate Satisfaction: a Case Study - Razali bin Mat Zin (Journal of Accounting and Investment, 2006)
The leadership literature is voluminous. This study adopted the contingency model to explain the relationship between the leader-subordinate similarity and subordinate satisfaction. The effects of selected intervening variables namely age, educational level, race and sex were also analyzed. The findings showed that there is a significant relationship between leader-subordinate similarity and subordinates’ satisfaction. However, this significance was determined only after accounting for the demographic variables, i.e. age, subordinates’ sex, race and educational level. Once the demographic variables were accounted for, the consideration and initiating structure dimensions of leadership showed significant relationship with subordinates’ satisfaction with work.